Clinical and radiographical analysis of percutaneous kyphoplasty with multi-point cement anchoring technique for preventing bone cement displacement in Kümmell’s disease of stage I and II - Wu, Heng; Dai, Xiao; Liu, Hao; Yang, Xiang; Liu, Shenao; Xu, Shuang; Chi, Hao; Chen, Yuquan; Wang, Song (Frontiers in Endocrinology, 2025)
BackgroundThe present study introduced a novel technique called percutaneous kyphoplasty with multi-point cement anchoring technique (A-PKP) to prevent bone cement displacement in patients with stage I and II Kümmell’s disease (KD).MethodsA total of 82 patients with stage I and II KD were treated with PKP in our hospital from April 2020 to October 2022. The patients were divided into two groups: A-PKP group (N=39) where the Kirschner needle was used for the multi-point cement anchoring technique, and conventional transverse process-pedicle percutaneous kyphoplasty group (T-PKP group; N=43) where the Kirschner needle was not used. The operation time, volume of cement, VAS score, ODI score, cement distribution pattern and score, bone cement leakage, adjacent vertebra fracture, and bone cement displacement were compared between the two groups. A logistic regression model was used to evaluate the association between outcome variables and adjacent vertebral fractures, as well as to identify potential protective and risk factors following kyphoplasty.ResultsAll patients in both groups were operated successfully, with no serious complications reported. Compared with T-PKP patients, A-PKP patients had longer operation time (39.7 ± 4.86 min vs. 34.5 ± 3.18 min, P < 0.05), greater volume of cement (5.1 ± 0.41 ml vs. 4.3 ± 0.27 ml, P < 0.05), greater improvement in Visual Analog Scale (2.0 ± 0.48, 1.92 ± 0.72 vs. 3.0 ± 0.10, 3.1 ± 0.62, P < 0.05) and Oswestry Disability Index scores (17.9 ± 2.38, 14.8 ± 2.02 vs. 20.2 ± 3.31, 17.2 ± 2.55, P < 0.05) during follow-ups, more spongy cement configuration with higher distribution scores (10.0 ± 1.17 vs. 7.74 ± 1.08, P < 0.05), lower incidence of bone cement leakage (20.5% vs. 27.9%, P > 0.05), and lower rate of adjacent vertebra fractures (5.1% vs. 18.6%, P < 0.05) and bone cement displacement (2.5% vs. 20.9%, P < 0.05). The logistic regression results reveal that bone cement distribution score (OR= 0.355, 95% CI 0.171–0.734, P=0.005) acts as protective factor of adjacent vertebral fractures following kyphoplasty.ConclusionThe A-PKP technique appears to be a safer and more effective alternative for patients with stage I and II KD. It effectively alleviates pain, enhances cement diffusion, and minimizes the risk of bone cement displacement compared with the T-PKP.